2013
DOI: 10.1136/bmjopen-2013-003101
|View full text |Cite
|
Sign up to set email alerts
|

Inspiratory muscle training protocol for patients with chronic obstructive pulmonary disease (IMTCO study): a multicentre randomised controlled trial

Abstract: IntroductionInspiratory muscle training (IMT) has been applied during pulmonary rehabilitation in patients with chronic obstructive pulmonary disease (COPD). However, it remains unclear if the addition of IMT to a general exercise training programme leads to additional clinically relevant improvements in patients with COPD. In this study, we will investigate whether the addition of IMT to a general exercise training programme improves 6 min walking distance, health-related quality of life, daily physical activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
1
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 45 publications
0
52
1
10
Order By: Relevance
“…These findings support the benefits found in subjects with multiple sclerosis 24 and COPD. 25 In addition, 3 cross-sectional studies were found [19][20][21] recommending the inclusion of respiratory muscle training in the PR program for subjects after stroke. The eligibility criteria do not contribute to the total score.…”
Section: Discussionmentioning
confidence: 99%
“…These findings support the benefits found in subjects with multiple sclerosis 24 and COPD. 25 In addition, 3 cross-sectional studies were found [19][20][21] recommending the inclusion of respiratory muscle training in the PR program for subjects after stroke. The eligibility criteria do not contribute to the total score.…”
Section: Discussionmentioning
confidence: 99%
“…More information about study procedures can be found in an extended ‘Materials and methods’ section and in a video tutorial (see online supplementary video files 1, 2, 3, and 4), as well as in a previously published study protocol 16…”
Section: Methodsmentioning
confidence: 99%
“…Training intensities during GET were progressively increased during the course of the programme based on symptom scores. Training intensities corresponded to Borg CR-10 scale ratings of 4–6 on dyspnoea sensation 16. Physiotherapists providing this intervention were blinded to group allocation of patients.…”
Section: Methodsmentioning
confidence: 99%
“…The basic difference between this tool and the others is its ability to offer the largest load during the therapy, and to adapt inspiratory resistance to the pressure x lung volume curve (13,37), which could generate load stabilization along the breath, by providing a feeling of comfort to the patient. Up until now this concept has a physiological basis.…”
Section: Introductionmentioning
confidence: 99%